Effect of Extrusion Temperature Variations for Manufacturing 3D Printer Filament Based on Used Bottle Waste on Impact Strength - Santosa Budiono, Herru; Purnomo, Sigit Joko (Politeknik Piksi Ganesha Indonesia, 2024)
Manufacturing 3d printer filaments based on used plastic bottle waste is a promising solution in reducing environmental impact while utilizing excessive available resources. This research aims to evaluate the effect of variations in manufacturing temperature (210°C, 220°C, and 230°C) on the impact strength of 3D printer filament based on used bottle waste. The experimental method was carried out by printing filament samples at each printing temperature and testing the impact strength using the Charpy method. The research results show that printing temperature affects the impact strength of the filament, with a temperature of 230°C providing optimal results.